Modulação do fenótipo de macrófagos associados a tumores como mecanismo de ação da atividade antitumoral/antimetastática de proteases obtidas do látex de Vasconcellea cundinamarcensis - Ariadne Duarte Braga (2017)
A proteolytic fraction (P1G10) from V. cundinamarcensis latex has antitumor/antimetastatic activity on 4T1 breast carcinoma model by reducing inflammation, angiogenesis and increasing tumor associated-macrophages (TAMs) activity. The aim of this study was to investigate the mechanisms of macrophages activation by P1G10 sub-fractions (CMS1 and CMS2) and the ability of these proteins to reduce tumor mass and metastasis number by in vivo modulation of TAM’s. First, was shown that the levels of nitrite and ROS were augmented in 2 and 11 times, respectively, after macrophage treatment with CMS1 or CMS2. Dosage of cytokines levels in theses cultures, revealed that CMS1 increases levels of IL-1β (586%), IL-6 (23%) and CCL2/MCP-1 (368%). The sub-fraction CMS2 promotes an increase of these same cytokines in 1.3, 2.8 and 0.8 times above the observed by CMS1 treated macrophages. The levels of IL-12 were increased by CMS1 treatment (180%) and TNF-α by CMS2 (88%). In the other hand, cytokines as VEGF, TGF- β and MMP-9 activity were diminished around 53, 94 and 95%, respectively, by exposing macrophages to both sub-fractions. CMS2 was able to promote the macrophage tumoricidal activity, as reduced 4T1 cell viability (57%) in a co-culture model. Although, CMS1 augments the levels of these inflammatory mediators it was not able to induce macrophage tumoricidal activity. After, was done analyzes of intracellular signaling pathways, that could be stimulated in macrophages by CMS2 treatment, as NFk-B, COX-2, MAPKs e Akt. The results revealed that Akt and NFk-B signaling are activated in macrophage by CMS2 proteins. After 22 days of treatment, CMS2 (0.3, 1.0 or 3.0 mg/kg, s.c) reduce, in all doses, the tumor weight (31%) and lung metastasis (48%) in 4T1 breast carcinoma model. The results shown that CMS2 (3.0 mg/kg), when compared to saline treated mice, decreases tumor levels of IL-1β at 31%, total TGF-β at 33%, VEGF at 34% and the activity of metalloproteinase-2 at 78% but increases IL-12 level at 25% and it wasn’t detected any alteration in levels of TNF-α, IL-10, or NAG-activity. So, we can conclude that CMS2 shows antitumor/antimetastatic activity, in some way, by modulation of TAMs while gives to these immune cells ability to fight tumor cells, directly by alterations in intra-signaling pathways or, indirectly, by cause alterations in the production of intratumoral mediators that can promote macrophage tumoricidal phenotype.